2022
DOI: 10.1039/d2sm00775d
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation dynamics of deformed polymer nanocomposites as revealed by small-angle scattering and rheology

Abstract: The relaxation dynamics of polystyrene (PS)/silica nanocomposites after a large step deformation are studied by a combination of small-angle scattering techniques and rheology. Small-angle x-ray scattering measurements and rheology show...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…[27][28][29][30][31][32][33] As was recalled above, we can go beyond the mechanical characterization because the interfacial properties of PNC can be probed by a large variety of scattering and microscopy techniques with the aim of identifying their characteristic length and time scales, for example, NMR, [3,10,11,34,35] differential scanning calorimetry (DSC), [36] dynamic mechanical thermal analysis (DMTA), [28,[37][38][39] rheology, [40,41] neutron and positron annihilation spectroscopies, [42,43] atomic force microscopy (AFM), [26,40] small-angle neutron (SANS), [42,43] and small-angle X-ray scattering (SAXS). [44][45][46] One important question in this field concerns the observed similarities amongst PNC. Transmission electron microscopy (TEM) indicated that CB exists as aggregates of spherical particles.…”
Section: Characterization Of the Interface Between Phases In Dense Po...mentioning
confidence: 99%
“…[27][28][29][30][31][32][33] As was recalled above, we can go beyond the mechanical characterization because the interfacial properties of PNC can be probed by a large variety of scattering and microscopy techniques with the aim of identifying their characteristic length and time scales, for example, NMR, [3,10,11,34,35] differential scanning calorimetry (DSC), [36] dynamic mechanical thermal analysis (DMTA), [28,[37][38][39] rheology, [40,41] neutron and positron annihilation spectroscopies, [42,43] atomic force microscopy (AFM), [26,40] small-angle neutron (SANS), [42,43] and small-angle X-ray scattering (SAXS). [44][45][46] One important question in this field concerns the observed similarities amongst PNC. Transmission electron microscopy (TEM) indicated that CB exists as aggregates of spherical particles.…”
Section: Characterization Of the Interface Between Phases In Dense Po...mentioning
confidence: 99%
“…In this sense, such model-free analysis of the scattering anisotropy fails to produce microstructural information that can be directly interpreted at the molecular level and compared to molecular models. Alternatively, mathematical approaches such as the method of spherical harmonic expansion have been developed to describe scattering anisotropy from deformed polymers, but require simplifying assumptions about the chain segment density distribution to obtain information about the molecular configuration. Therefore, the development of accurate, molecularly informed models for anisotropic scattering in deformation and flow is critically important for understanding the microstructural changes encoded in the anisotropic scattering patterns.…”
Section: Introductionmentioning
confidence: 99%